(untitled) (Malaysian Journal of Civil Engineering, 2018)
Measurement and monitoring of structural components such as beams and columns under loading are important in structural analysis and design assessment. Presently, the assessment on structural components on deformation or displacement measurement is carried out through LVDTs or dial gauges. The LVDTs or dial gauges were installed in contact with the structural components, also known as contact method. However, present contact method is subjected to some limitations such as s displacement points of measurement are highly depend on the position of LVDTs available, reliability of LVDTs and dial gauges to measure during the experiments due to possibility of damage sensors and consumption of time on the installation the sensors. Due to the limitations of contact method, this study demonstrates the use of a noncontact method using digital close range photogrammetry technique to measure the deformational behaviour of full-scale structural beams and columns. In this study, a full-scale load tests on structural components were performed under laboratory conditions. A series of digital images of the structural beams and columns under various loads were captured using Nikon DSLR cameras. The digital images then processed and analyzed using digital close range photogrammetric technique to measure and extract the magnitude of the structural beam and column displacements. The deformation and displacement of beam and columns have been validated by comparing the photogrammetric outputs against the results obtained from the LVDTs. The statistical analysis shows the differences obtained between the photogrammetric technique and contact method used were not significant.